International evidence on time-variation in trend labor productivity growth - Philipp Wegmüller (University of Bern, Department of Economics, 2016)
This paper provides international evidence on time-variation in trend productivity growth, based on the dataset for hours worked constructed by Ohanian & Raffo (2012). Applying both the endogenous break tests of Bai & Perron (1998, 2003) and the Stock & Watson (1996, 1998) TVP-MUB methodology, substantial evidence of time-variation in trend productivity growth is detected for most countries. For either Japan, or countries belonging to the Eurozone, evidence points towards a significant growth decline over the last several decades. Weaker evidence is reported for the United States, for which the 1990's productivity acceleration is estimated to have been overall mild, and of a temporary nature.
Keywords: E30; 330; Labor productivity; structural break tests; time-varying parameters; median-unbiased estimation; bootstrapping; Monte Carlo integration